Implementation of Organizational Citizenship Behavior Factory Family Members Joger's Words Factory - Oka Suryadinatha Gorda; I Made Pustika Mahendra; I Made Mai Noval (Universitas Pendidikan Ganesha, 2022)
The main factors of the success of an organization that HR provides are extra behavior and effectiveness in work. Extra behavior from human resources is needed by organizations to be able to help encourage the progress of an organization and this extra behavior is called Organizational Citizenship Behavior (OCB). This study aims to analyse the implementation of organizational citizenship behavior of family members of the Joger Words Factory. The literature used in this study consists of two theories, namely social exchange theory and Organizational Citizenship Behavior. The research focus plays an important role for researchers to make it easier to conduct research, with the aim of limiting studies in research conducted, especially on research objects so that the discussion does not expand and focus on research topics. There are three data collection techniques carried out in data collection in this study, namely: documentation interviews and observations. The selection of informants is carried out using the snowball sampling method. Testing the validity of the data in this study uses the triangulation method, which is a data examination method that utilizes something else in comparing the results of the interview with the object of the study. The triangulation used in this study includes source triangulation. The data analysis technique used in this study is interactive analysis. This model has 4 components of analysis, namely: data collection, data reduction, data presentation, and drawing conclusions. Implementation of Organizational Citizenship Behavior of Family Members Factory Joger’s words is seen from five indicators including Altruism, Conscientiousness, Courtesys, Sportsmanship and Civic Virtue.